Introduction of a boiling surface effectiveness parameter. (October 2022) - Harrison, Matt; Gess, Joshua
Abstract: Boiling is a complex heat transfer mechanism where surface area, material finish, working fluid and material properties, all have a drastic effect on the overall heat transfer coefficient. Currently in boiling heat transfer there is no standardized way to measure how effective a surface is at effectively transferring heat from a surface to the working fluid. This work proposes a new parameter that is based off experimental work and previously developed heat transfer effectiveness parameters to help more effectively compare standard and novel boiling surfaces efficacies against one another. This way design engineers can more effectively choose a surface that best meets their programmatic needs.